THE INFLUENCE OF PRODUCTION, CONSUMPTION AND FOREIGN EXCHANGE RESERVES ON RICE IMPORTS IN INDONESIA, 1993-2023 - Yustiti Ros Sianturi; Ni Putu Martini Dewi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Trade is a very important thing in a country's economic activities. The active trade activities of a country are an indication of the level of prosperity of its people, as well as a benchmark for the level of the country's economy itself. Through trade, a country can establish diplomatic relations with neighboring countries. Import activities carried out by Indonesia are one of the government's policies in the field of international trade. The difference between the amount of production and the amount of people's needs is one of the causes of implementing the import trade policy. The aim of this research is to determine the simultaneous and partial influence of Production, Consumption and foreign exchange reserves on rice imports in Indonesia from 1993-2023. The analysis technique used is multiple linear analysis, and data collection is used through time series with observations for the period 1993-2023. The analysis tool used is SPSS (Statistical Program For Social Science). The research results show that simultaneously the variables of production, consumption and foreign exchange reserves do not have a significant effect on rice imports in Indonesia in 1993-2023. Partially, the variables Production, Consumption and foreign exchange reserves do not have a significant effect on rice imports in Indonesia in 1993-2023.